2019
DOI: 10.1111/avj.12846
|View full text |Cite
|
Sign up to set email alerts
|

Treatment response and long term follow up in nineteen dogs diagnosed with chronic enteropathy in Australia

Abstract: Chronic enteropathy (CE) in dogs is common worldwide, but little data is available from Australia. The aim of this study was to describe treatment response and long‐term outcome in a cohort of dogs with CE. Dogs were prospectively enrolled at Murdoch University and the University of Melbourne. After diagnostic investigation to rule out diseases other than CE, dogs underwent sequential therapeutic trials until achieving a clinical response (diet then antibiotics, and finally immunosuppressants). Success was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 48 publications
2
28
1
Order By: Relevance
“…The poor long-term outcome in IRE and ARE dogs was also reported in a large study from the UK with significantly better outcome in dogs with FRE than ARE or IRE 4. Similar results are reported in a study from Australia with better outcome in dogs with FRE than ARE although the study was underpowered 53…”
Section: Response To Treatment For Chronic Enteropathysupporting
confidence: 83%
See 1 more Smart Citation
“…The poor long-term outcome in IRE and ARE dogs was also reported in a large study from the UK with significantly better outcome in dogs with FRE than ARE or IRE 4. Similar results are reported in a study from Australia with better outcome in dogs with FRE than ARE although the study was underpowered 53…”
Section: Response To Treatment For Chronic Enteropathysupporting
confidence: 83%
“…Finally, 7 studies reported outcomes in dogs with CE with a follow-up period greater than 6 months (Table 4). Most studies reported a good long term outcome in dogs responding to diet with remission rates of over 66% 46,49,5153. The effect of diet could not be assessed in one study as the diet was not changed in all dogs and additional treatment was used concomitantly 50.…”
Section: Response To Treatment For Chronic Enteropathymentioning
confidence: 99%
“…However, there is no standard treatment that offers the best strategy to adopt for this scope. Indeed, typical treatments involve sequential trials starting with the less invasive diet, followed by antibiotics and ultimately immune‐suppressive drugs in non‐responsive dogs or cats (Dandrieux, 2016; Dandrieux et al ., 2019).…”
Section: Therapeutic Strategies For the Treatment Of Inflammatory Bowmentioning
confidence: 99%
“…However, if the effectiveness of the use of antibiotics has been reported in case of infections, their real benefit to treat CE is uncertain since antibiotics are surrounded by many contradictions. Indeed, the employment of antibiotics can expose animals to risk factors such as a significant decline of the intestinal microbial biodiversity, reduction of beneficial bacteria and development of antibiotic‐resistant microorganisms (Suchodolski et al ., 2009; Dandrieux et al ., 2019; Werner et al ., 2020). Metronidazole and/or tylosin are the most commonly prescribed antibiotics to treat GI diseases (Mondo et al ., 2019).…”
Section: Therapeutic Strategies For the Treatment Of Inflammatory Bowmentioning
confidence: 99%
See 1 more Smart Citation